Cationic disordering modulated electrochemical performances of layer-structured Li2MoO3. (November 2021) - Liu, Zepeng; Zhang, Chu; Tian, Meng; Yang, Ruizhi; Gao, Yurui; Wang, Xuefeng; Wang, Zhaoxiang; Chen, Liquan
Abstract: Due to the intervolved oxygen loss and cation disordering upon lithium extraction at high potentials, it is difficult to recognize the reason for the performance decay in the conventional lithium-rich layered oxides (LLOs). Herein, we chose Li2 MoO3 as a prototype lithium-rich layered material to understand the effect of cationic disordering upon delithiation. On the basis of the density functional theory (DFT) calculations and performance characterization, we clarify that the local disorder structures of Li2 MoO3 modulate the sequence of Li extraction from different sites, which influences the properties of the material, such as capacity, charge compensation and electric conduction. These findings provide profound views in understanding the performance decay and structural design of LLOs for the Li-ion batteries. Graphical abstract: Image 1 Highlights: Most of types of the disordered Li2 MoO3 were listed and discussed. The properties of the disordered Li2 MoO3 were carefully analyzed through DFT calculations. The disordered Li2 MoO3 exhibit better electrochemical performance than that of the pristine Li2 MoO3 .